Effect of Computer Animations on Senior High School Students’ Learning Outcomes in Chemistry: A Focus on Rate of Reactions - Gloria Asiedu; Boniface Yaayin; Ruby Hanson (Language, Literature and Education: Research Updates Vol. 2, 2025)
Understanding many concepts in chemistry is difficult for most students because of its abstract nature. Chemistry teachers, notwithstanding the difficulties encountered by students, are making frantic efforts to make the rate of reactions less difficult and interesting to learn. Applications of teaching strategies such as the use of ICT in computer-assisted modes of teaching, cartoons and other innovative and interactive approaches need to be applied by teachers in their lesson executions to increase the effectiveness of chemistry learning for students. The significance of computer animations in a senior high chemistry classroom is investigated in this chemistry education research study. This study investigated the effect of computer animations on the academic achievements of senior high school students in terms of the rate of reactions. The study was conducted in two public Senior High Schools in Ablekuma West Municipal in the Greater Accra Region of Ghana. This study was anchored on the positivist paradigm and adopted the quantitative approach as well as a quasi-experimental design to achieve its objectives. The study used purposive sampling to select 85 students for the study. Two intact classes were engaged in the study with 45 students in the experimental group and 40 students in the control group. The instrument used for the collection of data was the ‘Rate of Reaction Achievement Test’ (RoRAT), in the form of a pre-test and a post-test. The pre-test was used to check if the two groups were at the same level of achievement in the rate of reactions or not before the treatment. A post-test was administered after the treatment to find out whether the treatment activities assisted in enhancing students’ academic achievement in the rate of reactions or not. The t-test analysis of the pre-test scores showed that the p-value was 0.960 which was greater than the 0.005 alpha value (p > 0.05). This means there was no significant difference between the means of the pre-test scores of the experimental group and the control group before the treatment, indicating that the two groups were the same in terms of their understanding and achievements in the rate of reaction concepts. However, from the t-test analysis of the post-test scores, the p-value was found to be 0.000 which was less than the 0.05 alpha value (p < 0.05). This shows that there was a statistically significant difference between the means of the post-test scores of the experimental group and the control group after the treatment. The effect size in the post-test scores between the two groups was large which was seen in the calculated Cohen’s D value of 2.176. The study concluded that computer animations assisted senior high school students to better understand the rate of reactions resulting in enhanced academic achievement. This research contributes to chemistry education by providing teachers and curriculum developers with an alternative instructional strategy which is the use of computer animation for teaching rate of reactions.